(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Teachers’ work in early childhood education is crucial to children’s development. Therefore, this demanding occupation can lead to health risks for educators, especially with regard to musculoskeletal disorders. Objective: The aim of this study was to investigate the prevalence and patterns of musculoskeletal disorders in early childhood teachers, in order to develop measures to promote the occupational health of these educators Methodology: This was a quantitative, exploratory and descriptive study of 29 early childhood teachers at levels I and II, covering children aged between 6 months and 3 years. The research used two structured questionnaires adapted for the Portuguese language, including the Nordic Osteomuscular Symptoms Questionnaire (NMQ). Results: The results indicate that musculoskeletal disorders are prevalent among early childhood teachers, affecting various regions of the body, such as the neck, shoulders, arms, forearms, hands, dorsal region, lumbar region and hip/MMII. The neck and shoulders are particularly affected, with most teachers associating the pain with their work. The most commonly used resources for dealing with pain were medication, gel ointment and massage. Conclusion: The discussion on musculoskeletal disorders in pre-school teachers highlights the relevance of this issue and the need for preventive and therapeutic actions to promote the occupational health of these professionals. Policies that encourage the adoption of appropriate postures and the conscious use of therapeutic resources are fundamental to ensuring a healthy and safe working environment for teachers.